Costs of epidural analgesia for delivery. Instituto Nacional Materno Perinatal, January 2006 - Arias Lazarte, Silvia E. (2010)
Objective: To determine unitary costs and operational costs, and to identify the elements and the most important variables when using epidural analgesia for labor. Material and method: Design: retrospective,descriptive,andcross-sectional study. Patients included were 53 women in labor. They received epidural analgesia for delivery in January 2006 at the Instituto Nacional Materno Perinatal (the main Maternity Hospital in Lima, Peru). The instrument used was a survey for estimating costs. Costs types are calculated using a methodology assessing information of hospital management, determining the percentage attributable for every variable, knowing expenses for every unit we calculated unitary expenses and total production costs. Results: Professional fees is a variable with the maximum weight, and it represents 74 % of costs within the whole service, therapeutic material and costs of clothing represent 14 %, and depreciation of medical equipments, furniture, and infrastructure represent 12 %.   Conclusion: Epidural analgesia during labor increases service costs in S/. 379.00, which is an affordable price for women in labor.